2012
DOI: 10.1111/j.1365-2672.2012.05376.x
|View full text |Cite
|
Sign up to set email alerts
|

Mode of action and safety of lactosporin, a novel antimicrobial protein produced by Bacillus coagulans ATCC 7050

Abstract: Aims To determine the mechanism of action of antimicrobial protein, lactosporin, against Gardnerella vaginalis and to evaluate its safety in vitro. Methods and Results Bacillus coagulans ATCC 7050 was grown at 37°C for 18 h. The cell‐free supernatant was concentrated 10‐fold and screened for antimicrobial activity against indicator strain Micrococcus luteus. The mode of action of lactosporin was determined by measuring the potassium release and monitoring the changes in transmembrane potential (Δψ) and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 34 publications
2
19
0
2
Order By: Relevance
“…2). Similar results have been reported for other bacteriocins with high ([10 kDa) molecular weight, thermoleovorins [7], thermophilin ST-1 [18], nigrecin [21], cerein 8A [22], lactosporin [23].…”
supporting
confidence: 88%
“…2). Similar results have been reported for other bacteriocins with high ([10 kDa) molecular weight, thermoleovorins [7], thermophilin ST-1 [18], nigrecin [21], cerein 8A [22], lactosporin [23].…”
supporting
confidence: 88%
“…Subtilosin A is a ribosomally synthesized and post-translationally modified antimicrobial peptide produced by B. subtilis and active against a variety of Gram-positive bacteria including the foodborne pathogen L. monocytogenes [14]. Riazi et al (2009) [15] reported lactosporin production from Bacillus coagulans isolated from a probiotic dietary supplement, Lactospore ® probiotic.…”
Section: Q2mentioning
confidence: 99%
“…This specific and limited spectrum of inhibition may be due to the synthesis of bacteriocin-like inhibitory substances (BLIS). Bacillus coagulans has been reported to produce coagulin and lactosporin as BLIS (23,35).…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Studies pertaining to the effects of proprietary B. coagulans such as GanedenBC30 TM preparation as a food ingredient on symptoms of diarrhea-predominant irritable bowel syndrome and assessment of safety of such kind of preparations have also been demonstrated in literature [10][11][12]. Bacillus coagulans preparations have been reported to produce bacteriocin-like inhibitory substances (BLIS) e.g., coagulin and lactosporin [23,35].…”
Section: Introductionmentioning
confidence: 96%